Limited role of murine ATM in oncogene-induced senescence and p53-dependent tumor suppression. - Alejo Efeyan; Matilde Murga; Barbara Martinez-Pastor; Ana Ortega-Molina; Rebeca Soria; Manuel Collado; Oscar Fernandez-Capetillo; Manuel Serrano (PLoS ONE)
Recent studies in human fibroblasts have provided a new general paradigm of tumor suppression according to which oncogenic signaling produces DNA damage and this, in turn, results in ATM/p53-dependent cellular senescence. Here, we have tested this model in a variety of murine experimental systems. Overexpression of oncogenic Ras in murine fibroblasts efficiently induced senescence but this occurred in the absence of detectable DNA damage signaling, thus suggesting a fundamental difference between human and murine cells. Moreover, lung adenomas initiated by endogenous levels of oncogenic K-Ras presented abundant senescent cells, but undetectable DNA damage signaling. Accordingly, K-Ras-driven adenomas were also senescent in Atm-null mice, and the tumorigenic progression of these lesions was only modestly accelerated by Atm-deficiency. Finally, we have examined chemically-induced fibrosarcomas, which possess a persistently activated DNA damage response and are highly sensitive to the activity of p53. We found that the absence of Atm favored genomic instability in the resulting tumors, but did not affect the persistent DNA damage response and did not impair p53-dependent tumor suppression. All together, we conclude that oncogene-induced senescence in mice may occur in the absence of a detectable DNA damage response. Regarding murine Atm, our data suggest that it plays a minor role in oncogene-induced senescence or in p53-dependent tumor suppression, being its tumor suppressive activity probably limited to the maintenance of genomic stability.